Double Glomerulonephritis in a Patient with Ankylosing Spondylitis Treated with Biologic Agent: Extrarticolar Involvement or Anti-Tumor Necrosis Factor Alpha Injury? A Case-Based Review. Issue 13 (November 2020) - Diena, Davide; Priora, Marta; Barreca, Antonella; Parisi, Simone; Colla, Loredana; Biancone, Luigi; Fusaro, Enrico
With the widespreading use of biologic drugs, reports of renal injury are increasing, most of which belong to the spectrum of secondary autoimmune syndromes. We present the case of a young man affected by Ankylosing Spondylitis, treated with tumor necrosis factor alpha inhibitors (Anti-TNF) that develop a peculiar renal damage: a coexistence of 2 glomerulonephritis due to different noxae, an IgA nephropaty with a Membranous nephropathy. The first one probably related to the rheumatologic disease, the second one related to Anti-TNF. Despite the underlying mechanisms, the renal involvement both related to Ankylosing Spondylitis and secondary to biologic treatment are currently rare and not predictable. Regular control of renal function and urinalysis during treatment with anti-TNF is mandatory. A concomitant treatment with Disease Modifying Anti Rheumatic Drugs or eventually a low dose of steroids may prevent the formation of anti-drug antibodies and could limit the renal damage related to this phenomenon.